Newborn screening for homocystinurias: Recent recommendations versus current practice. Issue 1 (11th February 2019) - Keller, Rebecca; Chrastina, Petr; Pavlíková, Markéta; Gouveia, Sofía; Ribes, Antonia; Kölker, Stefan; Blom, Henk J.; Baumgartner, Matthias R.; Bártl, Josef; Dionisi‐Vici, Carlo; Gleich, Florian; Morris, Andrew A.; et al.
Abstract: Purpose: To assess how the current practice of newborn screening (NBS) for homocystinurias compares with published recommendations. Methods: Twenty‐two of 32 NBS programmes from 18 countries screened for at least one form of homocystinuria. Centres provided pseudonymised NBS data from patients with cystathionine beta‐synthase deficiency (CBSD, n = 19), methionine adenosyltransferase I/III deficiency (MATI/IIID, n = 28), combined remethylation disorder (cRMD, n = 56) and isolated remethylation disorder (iRMD), including methylenetetrahydrofolate reductase deficiency (MTHFRD) ( n = 8). Markers and decision limits were converted to multiples of the median (MoM) to allow comparison between centres. Results: NBS programmes, algorithms and decision limits varied considerably. Only nine centres used the recommended second‐tier marker total homocysteine (tHcy). The median decision limits of all centres were ≥ 2.35 for high and ≤ 0.44 MoM for low methionine, ≥ 1.95 for high and ≤ 0.47 MoM for low methionine/phenylalanine, ≥ 2.54 for high propionylcarnitine and ≥ 2.78 MoM for propionylcarnitine/acetylcarnitine. These decision limits alone had a 100%, 100%, 86% and 84% sensitivity for the detection of CBSD, MATI/IIID, iRMD and cRMD, respectively, but failed to detect six individuals with cRMD. To enhance sensitivity and decrease second‐tier testing costs, we further adapted these decision limits using the data of 15 000 healthy newborns. Conclusions: Due to the favorable outcome of early treated patients, NBS for homocystinurias is recommended. To improve NBS, decision limits should be revised considering the population median. Relevant markers should be combined; use of the postanalytical tools offered by the CLIR project (Collaborative Laboratory Integrated Reports, which considers, for example, birth weight and gestational age) is recommended. tHcy and methylmalonic acid should be implemented as second‐tier markers.